A flipped classroom to personalise learning for engineering students. (19th August 2022) - Bui, Thi Thuy Hang; Kaur, Amrita; Hung, Tran Van
Flipped classrooms, also known as reversed or inverted classroom, has attracted widespread attention in higher education for active engagement and enhanced learning outcomes. It is proposed in the literature that flipped classroom promotes self-directed learning and can facilitate a personalised learning experience for students. The current study employed a pre-post experimental design to test the effectiveness of a soft skills course designed based on the flipped classroom model. A total of 155 (44 female, 111 male) students with a mean age of 20.35 years participated in this study. A paired t-test analysis showed significant differences in students' reports of self-directed learning, personalised learning, learning engagement, and assessment between pre-test and post-test. The findings have implications for promoting the flipped classroom model for engineering education students for enhanced engagement, acquisition of soft skills, and self-regulation.